The Impact of Judicial Digitalization on Access to Justice and Human Rights in Indonesia Post-Pandemic - Wala, Gevan Naufal (Journal of Law, Politic and Humanities, 2022)
This research examines the impact of judicial digitalization on access to justice and human rights protection in Indonesia following the COVID-19 pandemic. The study analyzes the implementation of digital court systems (e-court), virtual trials, and electronic case management systems that were accelerated during the pandemic period. Using normative-empirical legal research methodology, this study combines regulatory analysis, case studies of e-court implementation, and statistical data analysis from various court levels. The findings reveal that while digitalization has improved judicial efficiency, accessibility, and transparency, it has also created new challenges including digital divide, exclusion of vulnerable groups, and potential violations of fair trial principles. The research concludes that a balanced approach combining digital and physical court proceedings, supported by comprehensive regulatory frameworks and digital literacy programs, is essential to ensure digitalization enhances rather than undermines access to justice and human rights protection.